Chaos in the diagnosis of hepatitis C virus inhemodialysis patients (Journal of Renal and Hepatic Disorders, 2024)
Background: In India, a broad range of prevalence of Hepatitis C virus (HCV) infection in hemodialysis (HD) patients was reported. Variations in screening methods and regional differences in the HCV genome render challenges in the accurate detection of HCV. In this background, the present study was undertaken to assess the prevalence of HCV by HCV RNA PCR (Ribose nucleic acid Polymerase Chain Reaction) and HCV antibody detection by immunochromatography (ICT) and ELISA (Enzyme Linked Immuno-Sorbent Assay). Methods: A total of 50 patients with chronic kidney disease (CKD) on maintenance HD for more than six months were included in the study. Blood sample was collected and subjected to HCV RNA PCR, and HCV antibody by ICT and ELISA. Results: Of the 50 samples tested, ICT for HCV antibody was detected in 22 (44%) patients. They were positive for ELISA also. HCV RNA was positive in 15 (30%) patients. PCR positive was also positive for HCV antibody. Conclusions: This study concludes, that HCV antibody screening should be performed monthly and RNA PCR once every three months among HD patients.
Keywords: epatitis C virus; Hemodialysis; Antibody detection; Molecular method